Elites on trial - Morgan, Glenn; Hirsch, Paul; Quack, Sigrid (Emerald, 2015)
In 2008, the world entered a new period of turmoil. Financial markets collapsed, banks and other financial institutions went in to crisis; credit dried up, consumption reduced and firms started to cut back and reduce investment in the light of uncertainty. Unemployment increased and welfare payments increased. States that borrowed to save their banks and to maintain their spending found the financial markets and the international institutions condemning their profligacy and urging austerity policies. This book is concerned with what happens when elites are challenged by such a crisis; in our terms, elites are on trial firstly for their role in the past and shaping the context for the crisis, secondly in terms of how they responded to the crisis and finally in terms of what role they are playing in the aftermath. Can they reestablish their legitimacy or will they fail this trial and find themselves replaced by other groups with different objectives? This collection draws together a variety of studies and approaches to these issues from a group of international authors which helps us understand elites on trial in the contemporary period.
Keywords: Business & Economics -- Organizational Behavior.; Organizational theory & behaviour.; Elite (Social sciences); elektronické knihy; electronic books